Heavy Metals in Biota in Delaware Bay, NJ: Developing a Food Web Approach to Contaminants - Joanna Burger; Nellie Tsipoura; Larry Niles; Amanda Dey; Christian Jeitner; Michael Gochfeld (Toxics, 2019)
Understanding the relationship between heavy metal and selenium levels in biota and their foods is important, but often difficult to determine because animals eat a variety of organisms. Yet such information is critical to managing species populations, ecological integrity, and risk to receptors (including humans) from consumption of certain prey. We examine levels of cadmium, lead, mercury, and selenium in biota from Delaware Bay (New Jersey, USA) to begin construction of a “springtime” food web that focuses on shorebirds. Horseshoe crab (Limulus polyphemus) eggs are one of the key components at the base of the food web, and crab spawning in spring provides a food resource supporting a massive stopover of shorebirds. Fish and other biota also forage on the crab eggs, and a complex food web leads directly to top-level predators such as bluefish (Pomatomus saltatrix) and striped bass (Morone saxatilis), both of which are consumed by egrets, eagles, ospreys (Pandion haliaetus), and humans. Metal levels in tissues were generally similar in algae, invertebrates, and small fish, and these were similar to those in blood of shorebirds (but not feathers). There was a significant direct relationship between the levels of metals in eggs of horseshoe crabs and mean metal levels in the blood of four species of shorebirds. Metal levels in shorebird feathers were higher than those in blood (except for selenium), reflecting sequestration of metals in feathers during their formation. Levels in feathers of laughing gulls (Leucophaeus atricilla) were similar to those in feathers of shorebirds (except for selenium). Selenium bears special mention as levels were significantly higher in the blood of all shorebird species than in other species in the food web, and were similar to levels in their feathers. Levels of metals in bluefish and striped bass were similar or higher than those found in the blood of shorebirds (except for selenium). The mean levels of cadmium, lead, and mercury in the blood and feathers of shorebirds were below ...